2010
DOI: 10.5194/acp-10-3365-2010
|View full text |Cite
|
Sign up to set email alerts
|

Cloud condensation nuclei in polluted air and biomass burning smoke near the mega-city Guangzhou, China – Part 1: Size-resolved measurements and implications for the modeling of aerosol particle hygroscopicity and CCN activity

Abstract: Abstract. Atmospheric aerosol particles serving as Cloud Condensation Nuclei (CCN) are key elements of the hydrological cycle and climate. We measured and characterized CCN in polluted air and biomass burning smoke during the PRIDE-PRD2006 campaign from 1-30 July 2006 at a rural site ∼60 km northwest of the mega-city Guangzhou in southeastern China.CCN efficiency spectra (activated fraction vs. dry particle diameter; 20-290 nm) were recorded at water vapor supersaturations (S) in the range of 0.068% to 1.27%. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
372
2
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 328 publications
(449 citation statements)
references
References 82 publications
(86 reference statements)
58
372
2
9
Order By: Relevance
“…Studies have showed that internally mixed ECesulfate and OC-coated EC particles enhanced atmospheric absorption ability by increasing a particle's absorption efficiency by about 3 times compared to uncoated EC (Jacobson, 2001;Bond et al, 2006), and their ability as CCN by hydrophobic to hydrophilic surface alteration (Rose et al, 2010). Presented here are the first in situ chemically resolved measurements of the mixing state of biomass burning particles in the PRD Fig.…”
Section: Mixing State Of Biomass Burning Particles With Secondary Spementioning
confidence: 94%
“…Studies have showed that internally mixed ECesulfate and OC-coated EC particles enhanced atmospheric absorption ability by increasing a particle's absorption efficiency by about 3 times compared to uncoated EC (Jacobson, 2001;Bond et al, 2006), and their ability as CCN by hydrophobic to hydrophilic surface alteration (Rose et al, 2010). Presented here are the first in situ chemically resolved measurements of the mixing state of biomass burning particles in the PRD Fig.…”
Section: Mixing State Of Biomass Burning Particles With Secondary Spementioning
confidence: 94%
“…Nevertheless, particle number and size are expected to remain the major predictors for the variability of CCN concentration [Dusek et al, 2006;Rose et al, 2008b;Gunthe et al, 2009]. Reduced hygroscopicity of newly formed particles can be expected where SOA plays a major role in particle growth, e.g., over boreal and tropical forests [Tunved et al, 2006;Gunthe et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…The $10% higher value of k inorg obtained in this study can be attributed to the higher proportion of ammonium nitrate. For the prediction of CCN concentrations and the modeling of cloud droplet formation, however, such small differences in k are likely negligible [Rose et al, 2008b;Gunthe et al, 2009;Reutter et al, 2009].…”
Section: Dusek Et Al: Ccn During New Particle Formation Events L03804mentioning
confidence: 99%
“…The measurement data of the CCN efficiency spectra were corrected for differences in the CCNC and CPC counting efficiencies as described in Rose et al (2010), using a constant correction factor of 1.03. Moreover, a correction for multiply charged particles was performed according to .…”
Section: Size-resolved Ccn Measurementsmentioning
confidence: 99%
“…As a result of long-term efforts and recent advances in atmospheric research, the CCN activity of atmospheric aerosol particles can be fairly well constrained by measurements and models (e.g., Kreidenweis, 2007, 2008;Gunthe et al, 2009;Kinne, 2009;Moore and Nenes, 2009;Juranyi et al, 2010;Pringle et al, 2010;Rose et al, 2010;Wex et al, 2010;Gunthe et al, 2011;Kim et al, 2011;Kulmala et al, 2011;Rose et al, 2011;Spracklen et al, 2011;Anttila et al, 2012;Christensen and Petters, 2012;Engelhart et al, 2012;Padró et al, 2012;Jurányi et al, 2013;Lance et al, 2013;Mikhailov et al, 2013;Petters and Kreidenweis, 2013). To fully describe the process of CCN activation and cloud droplet growth in the atmosphere, however, the supersaturation of water vapor in the cloud also needs to be known (e.g., Reutter et al, 2009;Pruppacher and Klett, 2010;Rosenfeld et al, 2012;Renno et al, 2013).…”
Section: Introductionmentioning
confidence: 99%